INTELLECTUAL CAPITAL AND FIRM PERFORMANCE: THE EMERGENCE OF KNOWLEDGE BASED ECONOMY - Aleem, Muhammad; Haqqani, Kanwal (The journal of contemporary issues in business and government, 2021)
In the last few decades ‘intellectual capital’ has been among the most investigated constituent of corporate finance and accounting research. The immense empirical and theoretical research published in different journals, for instance, “Measuring Business Excellence” and the development and formation of specific journal, such as, “Journal of Intellectual Capital” are the evidence of this novel and emergent area of research. After the 1997 Asian financial crisis and the great financial crisis of 2008, the significance and magnitude of IC increase. The motive behind the critical role of IC during financial instability and disorder is that when companies are economically vulnerable and troubled during the financial disorder, the firms consider and explore alternative approaches of survival, such as, the use of intangible assets and resources.